Fraud analytics : strategies and methods for detection and prevention - Spann, Delena D. (New Jersey : Wiley, 2014)
"Proven guidance for expertly using analytics in fraud examinations, financial analysis,auditing and fraud preventionFraud Analytics thoroughly reveals the elements of analysis that are used in today'sfraudexaminations, fraud investigations, and financial crime investigations. This valuable resourcereviews the types of analysis that should be considered prior to beginning an investigation andexplains how to optimally use data mining techniques to detect fraud. Packed with examples andsample cases illustrating pertinent concepts in practice, this book also explores the two majordata analytics providers: ACL and IDEA. Looks at elements of analysis used in today's fraud examinations Reveals how to use data mining (fraud analytic) techniques to detect fraud Examines ACL and IDEA as indispensable tools for fraud detection Includes an abundance of sample cases and examples Written by Delena D Spann, Board of Regent (Emeritus) for the Association of CertifiedFraud Examiners (ACFE), who currently serves as Advisory Board Member of the Association ofCertified Fraud Examiners, Board Member of the Education Task Force of the Association ofCertified Anti-Money Laundering Specialists ASIS International (Economic Crime Council) andAdvisory Board Member of the Robert Morris University (School of Business), FraudAnalyticsequips you with authoritative fraud analysis techniques you can put to use right away"--
Includes bibliographies and Index.
Keywords: Fraud; Fraud investigation; Fraud -- Prevention; BUSINESS & ECONOMICS / Auditing